IMPELEMENTASI PRINSIP KEHATI-HATIAN DALAM PENERBITAN SERTIFIKAT HAK MILIK ATAS TANAH DI BPN PASANGKAYU - Rina Guntur (LEGAL OPINION, 2024)
Author’s conclusion: To find out the application of the precautionary principle in the issuance of land rights certificates can be seen from the land services provided by the Pasangkayu Land Office, which refers to the Regulation of the Head of the National Land Agency of the Republic of Indonesia Number 1 of 2010 concerning Service Standards and Land Regulations. The procedure for issuing a certificate of activity includes examination of juridical data and examination of technical data, for examination of juridical data such as the fulfillment of the required requirements, then this examination is carried out administratively / formal examination of existing documents. While for technical data examination which is an activity of measurement and determination of boundaries should be done in the field by visiting, measuring and determining boundary marks. Kesimpulan penulis: Untuk mengetahui penerapan prinsip kehati-hatian dalam penerbitan sertifikat hak atas tanah dapat dilihat dari layanan pertanahan yang diberikan oleh Kantor Pertanahan Pasangkayu, yang mengacu pada Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 1 Tahun 2010 tentang Standar Pelayanan Dan Pengaturan Pertanahan. Prosedur penerbitan sertifikat kegiatannya meliputi pemeriksaan data yuridis dan pemeriksaan data teknis, untuk pemeriksaan data yuridis seperti pemenuhan persyaratan yang diharuskan, maka pemeriksaan ini dilakukan secara administrsi/pemeriksaan formal dari dokumen yang ada. Sedang untuk pemeriksaan data teknis yang merupakan kegiatan pengukuran dan penetapan batas seharusnya dilakukan secara lapangan dengan mendatangi, melakukan pengukuran dan penetapan tanda batas.